Fatigue properties of TiNi shape memory alloy and applications to a heat engine and an actuator - Tobushi, H.; Nakahara, T.; Hashimoto, T.; Shimeno, Y.; Tanaka, K. (Archives of Mechanics, 1999)
The fatiue properties of a TiNi shape-memory alloy (SMA) wire in the region of the marteusitic transformation and the R-phase transformation are investigated. The rotating-bending fatigue life of a wire in the region of the R-phase transformation is longer than 107 cycles. A tilt-disk offset SMA heat engine and an indirect-heated SMA thermal actuator are developed.